SUBSTRATES AND NAPHTALENE ACETIC ACID CONCENTRATIONS ON ROOTING OF Calliandra selloi AND Calliandra tweediei SEMIHARDWOOD CUTTINGS - Lima, Daniela Macedo; Alcantara, Giovana Bonfim de; Bortolini, Michele Fernanda; Fanti, Fernanda Pereira; Biasi, Luiz Antonio; Quoirin, Marguerite; Koehler, Henrique Soares; Zuffellato-Ribas, Katia Christina (Scientia Agraria, 2006)
Caliandras (Fabaceae family, Mimosoideae subfamily) have inflorescences with exotic aspect and a great quantity of coloured stamens. The main objective of this study was to study the effect of naphthalene acetic acid (NAA) on rooting of cuttings of Calliandra selloi (with rose and white stamens) and C. tweediei (with red stamens), planted in two substrates. The cuttings were made from semi-hardwood ramifications of trees growing in Curitiba, Paraná, Brazil. They were 8 cm long, with 4 leaflets at the apical portion and they were carried out under climatized greenhouse (25o C ± 2o C, 95% RU). They were made two experiments with these species: in the first, the effect of different substrates was tested (carbonized rice hull and vermiculite) and, in the second, the base of the cuttings was immersed in NAA solutions (0, 1,500 and 3,000 mg.L-1) for 10 sec, and planting them in plastic tubes containing carbonized rice hull and vermiculite. After 60 days the following variables were evaluated: the percentage of rooted cuttings, of cuttings with callus, of alive and necrotic cuttings and the length and number of roots per cutting. The statistical analysis showed no interaction between the main (substrates x NAA concentrations and substrates x species), and carbonized rice hull was the best substrate for rooting percentage (rose C. selloi – 90.00%, white C. selloi – 73.34% and red C. tweediei – 11.67%). There was no difference among the results of rooting with the applied concentrations of NAA.